The Influence of Law on the Success of Zero Waste Program in Bali (Case Study of Waste Management at Pamanku Lestari Kuta Waste Bank) - Asrilindia Dewi, Ni Nyoman Mecin; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Bali is experiencing an increase in waste, mainly due to the growth in the number of tourists. The waste problem can have several negative impacts on the environment. Although the government has implemented various policies and regulations to reduce waste, their implementation is often hampered, either due to a lack of public awareness or unclear law enforcement. Pamanku Lestari Waste Bank is present as one of the community initiatives that supports Bali's vision of becoming a waste-free island. The purpose of this study is to analyze the extent to which regulations and laws related to waste management influence the success of the zero waste program in Bali. The method used is a qualitative approach with in-depth interview techniques with waste bank managers, community members, and related parties such as local governments as well as secondary data analysis from applicable policy documents. The discussion of the study shows that strong legal implementation and support from the local community play a significant role in the success of the zero waste program. However, challenges remain, especially in terms of consistent enforcement of regulations and guidance to the community regarding the correct way to manage waste. Pamanku Lestari Waste Bank has proven to be an effective model in increasing public environmental awareness, but clear and consistent policy support from the government is needed so that similar programs can be expanded. This research contributes to understanding the relationship between law and the effectiveness of community-based zero waste initiatives in Bali, as well as the importance of collaboration between government and communities to achieve environmental sustainability